ETHNONURSING: CULTURAL CARE IN A MAPUCHE COMMUNITY IN PUERTO AGUIRRE, AYSÉN, CHILE - Mansilla Ojeda, Marisa Angélica; Heidemann, Ivonete Teresinha Schulter Buss; Villa, Sergio Eduardo Contreras (My University, 2020)
ABSTRACT Objectives: to understand the beliefs, expressions, and practices of generic care used by the Mapuche community in Puerto Aguirre and acknowledge the professional care offered to promote health. Method: a qualitative research based on ethnonursing carried out during seven trips to Puerto Aguirre between July 2018 and January 2019. A total of seven key informants and seven general informants were interviewed. Information was collected through observations, field notes, conversations, and interviews. Results: the scientific property of ethnonursing was verified. Three themes that structure the cultural care practices in the studied community emerged: Mapuche identity as the main value to preserve cultural care; The essesntial presence of women to carry out meaningful experiences and care practices among the Mapuche; and Mapuche value and use of cultural and professional care practices to promote health. Conclusion: the research recognizes the full validity of the Cultural Care Theory. Nursing and, in general, the different health professions tend to become popular, and professional knowledge is complemented, thus learning and improving cultural care in the community.
Keywords: transcultural nursing; care; ethnic groups; anthropology, cultural; nursing research